MAKING EFFECTIVE ORAL PRESENTATIONS IN ESL - Dinora Sodiqova (International Scientific and Current Research Conferences, 2023)
Experts, believing that acquiring the knowledge of finer performance might be considerably practical, highlight the significance of an oral presentation in contemporary professionalism; however, a number of challenges are inevitable to reach a perfect demonstration of that. This article focuses on the importance of oral presentations in English as Second Language (ESL) settings and emphasizes the need for effective communication skills in today's globalized world, mentioning key aspects that contribute to successful oral presentations, such as organization, clarity, delivery techniques, visual aids, and self-evaluation. Additionally, it briefly explains the benefits of incorporating technology and providing opportunities for practice and feedback, setting the stage for exploring strategies and techniques to enhance oral presentation skills in ESL learners.